1998
DOI: 10.1007/pl00009573
|View full text |Cite
|
Sign up to set email alerts
|

Fiberoptic Endoscopic Documentation of the High Incidence of Aspiration following Extubation in Critically Ill Trauma Patients

Abstract: The purpose of this study was to investigate the incidence of aspiration following extubation in critically ill trauma patients. This prospective pilot study included 20 consecutive trauma patients who required orotracheal intubation for at least 48 hours. All subjects underwent a bedside transnasal fiberoptic endoscopic evaluation of swallowing at 24 +/- 2 hr after extubation to determine objectively aspiration status. Aspiration was defined as the entry of a blue dyed material into the airway below the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
9

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 33 publications
4
75
0
9
Order By: Relevance
“…These include oropharyngeal neuromuscular and sensory deficits, cognitive-communication, and behavioral impairments, [5,8,9,29,33] physical injury to the head and neck regions [12], medications [5,34], other concomitant injuries and prolonged endotracheal ventilation [12,[34][35][36][37][38][39]. Tracheostomies, while not causing dysphagia on their own [37][38][39], are common in this population and will also be discussed.…”
Section: Dysphagia Resulting From Tbimentioning
confidence: 99%
See 3 more Smart Citations
“…These include oropharyngeal neuromuscular and sensory deficits, cognitive-communication, and behavioral impairments, [5,8,9,29,33] physical injury to the head and neck regions [12], medications [5,34], other concomitant injuries and prolonged endotracheal ventilation [12,[34][35][36][37][38][39]. Tracheostomies, while not causing dysphagia on their own [37][38][39], are common in this population and will also be discussed.…”
Section: Dysphagia Resulting From Tbimentioning
confidence: 99%
“…Prolonged endotracheal tube (ETT) and ventilation places non-TBI trauma patients at an increased risk of silent and overt aspiration, however, this risk is transient [35], with dysphagia resolving in 2-5 days post-extubation [34,35,48]. Such dysphagia in trauma patients with prolonged ETT intubation is often multifactorial [35], resulting from prolonged contact of the ETT with chemo-and/or mechanoreceptors in the pharyngeal and laryngeal mucosae, critical for triggering the swallowing reflex [34].Physical injury including vocal fold ulceration and laryngeal edema [36] and impaired laryngeal elevation and/or closure may impede swallowing function [12].…”
Section: Prolonged Endotracheal Intubation and Ventilationmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Debate exists about the affect of nasogastric feeding tubes (present at the time of decannulation in subjects B and D) on the incidence of aspiration. Cameron et al 14 and Leder et al 26,27 note no increase in aspiration, whereas other authors have found a significantly increased incidence of aspiration, particularly of gastric contents. 10,28 Effects of 48 h of endotracheal intubation on swallow function have been shown to be significant, with aspiration rates as high as 56%, and up to 25% presenting without outward symptoms (silent aspiration).…”
Section: Discussionmentioning
confidence: 93%